Microbial Fuel Cells: A Dual Approach for Environmental Pollution Mitigation and Microenergy Production - Giandra Adiwilaga (Institute of Computer Science (IOCS), 2023)
This research delves into the multifaceted capabilities of Microbial Fuel Cells (MFCs) as pioneering tools at the nexus of environmental science and sustainable energy. With a dual focus on addressing environmental pollution and generating microenergy, the study explores the versatility and potential applications of MFCs across varied environmental matrices. Simulated scenarios encompassing water, soil, and air pollution elucidate the remarkable pollutant removal efficiencies of MFCs, highlighting their adaptability and effectiveness in diverse contexts. Intricate DNA sequencing analyses provide novel insights into the microbial community dynamics within MFCs, contributing to the evolving field of microbial ecology. The study reveals key microorganisms orchestrating electrochemical processes, furthering our understanding of the symbiotic relationships vital for MFC functionality. This microbial insight enhances the broader discourse on the role of microorganisms in bioelectrochemical systems. Practical guidelines for optimizing MFC performance are derived from systematic manipulations of operational parameters, electrode materials, and microbial consortia. This optimization framework not only refines MFC technology within the laboratory setting but also provides a tangible roadmap for practical implementations in real-world environmental contexts. The research pioneers the exploration of microenergy production at the microscale using MFCs.